Introducing Unplugged Coding to Teachers to Support Coding and Artificial Intelligence (AI) Learning at SD Negeri 27 Paukiri: Pengenalan Koding Unplugged Kepada Guru untuk Mendukung Pembelajaran Koding dan Kecerdasan Artifisial (KKA) di SD Negeri 27 - Ilman Indra Ansyari; A. Zam Immmawan Alam; Firdha Razak; Dideng Kadir; Ramli Ely (Yayasan Ahmar Cendekia Indonesia, 2026)
Digital education transformation requires elementary school teachers to possess digital literacy and computational thinking skills; however, teachers in remote areas are generally unfamiliar with the concept of unplugged coding. This community service (PKM) project aims to enhance teachers' understanding and skills in designing simple learning media without digital devices at SD Negeri 27 Paukiri, Pangkajene, and Kepulauan Regency. The method employed is a participatory approach involving training, demonstrations, practice, and mentoring, with qualitative descriptive data analysis. The results indicate a significant shift in teachers' perception that coding can be taught without computers, alongside an improvement in their skills in creating media from local materials. Implementation among students in grades I–VI also demonstrated high learning enthusiasm. It is concluded that unplugged coding is an effective and contextual solution for enhancing digital literacy in schools with limited facilities.